Estimating the burden of rheumatoid arthritis in Africa: a systematic analysis - Ben Dowman; Ruth M. Campbell; Lina Zgaga; Davies Adeloye; Kit Yee Chan (Edinburgh University Global Health Society, 2012)
Rheumatoid arthritis (RA) has an estimated worldwide prevalence of 1%. It is one of the leading causes of chronic morbidity in the developed world, but little is known about the disease burden in Africa. RA is often seen as a minor health problem and has been neglected in research and resource allocation throughout Africa despite potentially fatal systemic manifestations. This review aims to identify all relevant epidemiological literature pertaining to the occurrence of RA in Africa and calculate the prevalence and burden of disease.